1988
DOI: 10.1111/j.1432-1033.1988.tb14305.x
|View full text |Cite
|
Sign up to set email alerts
|

Catalase‐dependent ethanol oxidation in perfused rat liver

Abstract: The purpose of this study was to measure rates of catalase-dependent ethanol uptake and rates of HzOz generation in perfused rat livers in the presence of fatty acids of varying chain length. Rates of ethanol uptake in livers from fasted rats, perfused in a recirculating system, of about 80 pmol g-' h-' were decreased to about 10 pmol g-' h-' by the addition of an inhibitor of alcohol dehydrogenase (ADH), 4-methylpyrazole. The medium-chain-length fatty acid, laurate (12 : 0; 1 mM), increased rates of 4-methylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 42 publications
3
13
1
1
Order By: Relevance
“…Lower rates of mitochondrial poxidation in piglet liver suggest that entry of palmitate into mitochondria may have been limited by carnitine palmitoyltransferase I (EC 2.3.1.21) activity. However, the progres sively increased CCF production with in crease of palmitate concentration and the greater ratio of CCF production to mitochon drial P-oxidation in piglet liver (33.7%) than in adult pig liver (13.1 %) at 1.0 mM palmitate may indicate an intramitochondrial limita tion of ketogenesis in the neonate, as suggest ed elsewhere [3,4], Our results for rats are in general agree ment with earlier work suggesting that peroxi somal p-oxidation in liver increases more slowly than mitochondrial P-oxidation as the concentration of free fatty acids or fatty acylCoA increases [10,26,27], Others have noted that total oxidation of palmitate by isolated rat hepatocytes increased as the concentration of palmitate in the medium increased [26], We found that 14CO: production and total mitochondrial P-oxidation in rats increased as the palmitate concentration increased to 1.0 mM, but the ratio of 14CC>2 production to mitochondrial P-oxidation was <25% and generally decreased with increase of palmitate concentration. These results suggest that re sponses of mitochondrial p-oxidation to in 290 Biol Neonate 1997;72:284-292…”
Section: ß-Oxidation In Piglet Liversupporting
confidence: 82%
See 1 more Smart Citation
“…Lower rates of mitochondrial poxidation in piglet liver suggest that entry of palmitate into mitochondria may have been limited by carnitine palmitoyltransferase I (EC 2.3.1.21) activity. However, the progres sively increased CCF production with in crease of palmitate concentration and the greater ratio of CCF production to mitochon drial P-oxidation in piglet liver (33.7%) than in adult pig liver (13.1 %) at 1.0 mM palmitate may indicate an intramitochondrial limita tion of ketogenesis in the neonate, as suggest ed elsewhere [3,4], Our results for rats are in general agree ment with earlier work suggesting that peroxi somal p-oxidation in liver increases more slowly than mitochondrial P-oxidation as the concentration of free fatty acids or fatty acylCoA increases [10,26,27], Others have noted that total oxidation of palmitate by isolated rat hepatocytes increased as the concentration of palmitate in the medium increased [26], We found that 14CO: production and total mitochondrial P-oxidation in rats increased as the palmitate concentration increased to 1.0 mM, but the ratio of 14CC>2 production to mitochondrial P-oxidation was <25% and generally decreased with increase of palmitate concentration. These results suggest that re sponses of mitochondrial p-oxidation to in 290 Biol Neonate 1997;72:284-292…”
Section: ß-Oxidation In Piglet Liversupporting
confidence: 82%
“…Previous reports indicated increased ketogenesis by perfused rat liver as the concentration of oleate in the perfusate increased [27], Because we used fed rats, the response of mitochon drial ß-oxidation to increasing palmitate may be confounded to some degree by progressive ly greater inhibition of acetyl-CoA carboxy lase (EC 6.4.1.2) as palmitate or palmitoylCoA concentrations increased, which could lead to decreased concentrations of malonylCoA and thus greater flux through carnitine palmitoyltransferase I [13]. We found that the percentage contribution of peroxisomal ß-oxidation to total ß-oxidation capacity in rats was highly dependent on substrate concentration.…”
Section: ß-Oxidation In Piglet Livermentioning
confidence: 99%
“…Furthermore, peroxisomal β-oxidation is limited by substrate availability. In fact, it has been shown that treatment with peroxisome proliferators increased H 2 O 2 in vitro, but not in the perfused liver because fatty acid supply is rate-limiting in intact cells [35,36]. Indeed, the timing of the increases in radical production observed in this study did not correlate with that for the induction of ACO protein level and activity.…”
Section: Direct Evidence For Peroxisome Proliferator-induced Sustainecontrasting
confidence: 70%
“…As to the mechanism by which iron accumulation may interfere with hepatocyte function, most studies focus on the avidity with which iron may accelerate the formation of toxic oxygen species [121]. Iron and ethanol have additive effects on lipid peroxidation [121][122][123]. A possible sequence of reactions is the following: intake of ethanol produces NADH via alcohol dehydrogenase, this in turn mobilizes iron from ferritin, and non-haem iron thus mobilized catalyses the production of toxic oxygen species, of which OH is the most potent.…”
Section: Transferrin and Alcoholic Liver Diseasementioning
confidence: 99%